SERBIAN INSURANCE MARKET – SELECT ISSUES - Obadovic, Mirjana; Avdaliovic, Veselin; Obadovic, Milica (Economic Annals, 2010)
Every day insurance companies face a number of risks arising from the insurance industry itself, as well as risks arising from insurance company operations. In this constant fight against risks insurance companies use different models and methods that help them better understand, have a more comprehensive view of, and develop greater tolerance towards risks, in order to reduce their exposure to these risks.The model presented in this paper has been developed for implementation in insurance risk management directly related to insurance company risk, i.e. it is a model that can reliably determine the manner and intensity with which deviations in the initial insurance risk assessment affect insurance company operations, in the form of changes in operational risks and consequently in insurance companies’ business strategies. Additionally we present the implementation of the model in the Serbian market for the period 2005 - 2010.